Percepción de los pacientes sobre la calidad del cuidado invisible del profesional de Enfermería de los servicios de medicina y cirugía del Hospital II de Vitarte-EsSalud, 2011 - Hinostroza Figueroa, Jenny Raquel (2019)
Determine the perceptions of patients about the quality of care invisible nursing professional services Medicine andSurgery “Vitarte Hospital II-Beacon Healthcare Network.” The study is a non-experimental quantitative, descriptiveand transversal. The sample consisted of 62 patients in the service of medicine and surgery, we used an intentionalnon-probability sampling, where the instrument is applied to meet the criteria for inclusion and exclusion. Thecollection instrument was a questionnaire of 27 items, divided into six dimensions. The technique used was theinterview. The results obtained were in the service of medicine, 60% perceived the quality of care provided by theinvisible nurse as excellent, 40% perceived it as fair, on the other hand, in the service surgery, 53.1% perceived itas excellent, and only 6.3%, as deficient. In conclusion we can say that in both hospitals, most patients perceive asexcellent quality of care invisible.